2011
DOI: 10.2500/ajra.2011.25.3573
|View full text |Cite
|
Sign up to set email alerts
|

RNA-containing Exosomes in Human Nasal Secretions

Abstract: This study shows for the first time that NLF contains exosomes and that these exosomes contain RNA. Further characterization of the exosomal RNA and proteins may provide important information about communication in the nose and potentially provide a source of biomarkers for upper airway diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 29 publications
2
74
0
2
Order By: Relevance
“…While the majority of microRNAs are found and mediate their regulatory effects on gene expression intracellularly, a number of microRNAs are also present in the extracellular milieu and in various biological fluids of the human body, such as maternal milk [34][35][36][37][38], saliva [39,40], urine [41], nasal secretions [42,43], sperm [44] and plasma [45][46][47][48], and may represent interesting biomarkers of diseases [49,50].…”
Section: Extracellular Micrornas In the Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of microRNAs are found and mediate their regulatory effects on gene expression intracellularly, a number of microRNAs are also present in the extracellular milieu and in various biological fluids of the human body, such as maternal milk [34][35][36][37][38], saliva [39,40], urine [41], nasal secretions [42,43], sperm [44] and plasma [45][46][47][48], and may represent interesting biomarkers of diseases [49,50].…”
Section: Extracellular Micrornas In the Circulationmentioning
confidence: 99%
“…microRNAs are present in all the biological fluids of the human body, such as saliva [39,40], urine [41], nasal secretions [42,43], sperm [44] and plasma [45][46][47][48], which are relatively easy to collect from patients. Can monitoring of platelet-specific MPs and microRNAs in biological samples collected from patients help establish correlations between a given microRNA and specific diseases or conditions, and identify a more sensitive biomarker [89]?…”
Section: Use Of Platelet Mps and Micrornas As Biomarkers Of Diseasementioning
confidence: 99%
“…Since the first discovery of exosomes, a wide range of cells have been shown to release these vesicles. Exosomes have also been detected in several biological fluids, including plasma, nasal lavage fluid, saliva and breast milk [3][4][5][6] . Furthermore, it has been demonstrated that the content and function of exosomes depends on the originating cell and the conditions under which they are produced.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, exosomes originate from the inward budding of early and late endosomes hence forming MVBs containing ILVs [21,22]. Subsequently, the MVBs are transported to and fuse with the plasma membrane, requiring a dynamic interplay between members of the Rab and SNARE protein family, concurrently releasing the ILVs in the extracellular space [23][24][25][26][27]. Partly because both biogenesis pathway are analogous, to date there is no defined panel of markers to distinguish between both vesicle subtypes in a vesicular isolate.…”
Section: Biogenesis Cargo Loading and Compositionmentioning
confidence: 99%
“…EVs have been isolated from e.g. urine [11], plasma [26], semen [25], nasal secretion [24], breast milk [221], the aqueous humor of eyes [222], cerebrospinal fluid [223], peritoneal fluid [224], bronchoalveolar lavage [225]. Depending on the respective disease for which the biomarker is being developed, an accessible biofluid should be considered in which the EVs of interest are likely the most concentrated and a liquid biopsy can be easily obtained.…”
Section: 2evs As Biomarkermentioning
confidence: 99%